1999
DOI: 10.1590/s0100-72031999000200009
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez e Tumor Filodes Bilateral: Uma Associação Rara

Abstract: 109Relato de Caso 21 (2): 109-111, 1999 RBGO Introdução O tumor filodes, também denominado cystosarcoma phyllodes em razão das projeções foliácias de tecido tumoral no interior de cavidades císticas, é uma neoplasia mista de tecido epitelial e conectivo, caracterizando-se por um crescimento rápido e podendo apresentar grandes dimensões no momento do diagnóstico 1,3,7,8,9 . É um tumor raro, representando 0,5% de todos tumores mamários. A recidiva é freqüente porém raramente metastatiza e, quando isto ocorre, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Previous studies indicated occurrence of phyllodes tumors during pregnancy or lactation as benign, borderline or malignant, and unilateral or bilateral in 14 cases. 1,416 The findings of the present case of benign phyllodes tumor with lactational changes is concurrent with a case described previously by Likhitmaskul et al 1 in a 36-year-old pregnant woman who underwent mastectomy 3 weeks postpartum. Generally, phyllodes tumor presents as a relatively circumscribed painless mass.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies indicated occurrence of phyllodes tumors during pregnancy or lactation as benign, borderline or malignant, and unilateral or bilateral in 14 cases. 1,416 The findings of the present case of benign phyllodes tumor with lactational changes is concurrent with a case described previously by Likhitmaskul et al 1 in a 36-year-old pregnant woman who underwent mastectomy 3 weeks postpartum. Generally, phyllodes tumor presents as a relatively circumscribed painless mass.…”
Section: Discussionsupporting
confidence: 88%
“…summary of case reports of Phyllodes tumor occurring during pregnancy/lactation 1,[4][5][6][7][8][9][10][11][12][13][14][15][16]. …”
mentioning
confidence: 99%
“…Three articles were in languages other than English and French, consisting of Spanish, 16 Polish, 17 and Portuguese. 18 The first two 16,17 had English abstracts which were used for data extraction. The other one 18 was translated to English via three online translator software including Google translate (https://translate.google.com), Yandex translate (https://translate.yandex.com/translator), and SYSTRAN (http://www.systransoft.com/lp) in order to obtain a more accurate translation and data.…”
Section: Search Resultsmentioning
confidence: 99%
“…18 The first two 16,17 had English abstracts which were used for data extraction. The other one 18 was translated to English via three online translator software including Google translate (https://translate.google.com), Yandex translate (https://translate.yandex.com/translator), and SYSTRAN (http://www.systransoft.com/lp) in order to obtain a more accurate translation and data. There were six case series which included one PT in pregnancy each, three of which contained enough data and were included.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation